AB0809 Proteinuria in systemic sclerosis: Reversal by ACE inhibition. (23rd January 2014) - Schuster, J.; Moinzadeh, P.; Kurschat, C.; Benzing, T.; Krieg, T.; Weber, M.; Hunzelmann, N.
Abstract : Background: In systemic sclerosis (SSc) kidney damage is a major clinical problem which can lead to a deleterious outcome. In diabetes mellitus, early detection of proteinuria and treatment with angiotensin converting enzyme inhibitors (ACE) inhibitors has been shown to slow progression of kidney disease and to improve prognosis. Objectives: To investigate the spontaneous course of proteinuria and the effects of ACE inhibitor therapy in SSc patients. Methods: Proteinuria was determined in SSc patients with urine protein electrophoresis. SSc patients with proteinuria (n=31) were followed over a median of 12 months. Results: Of all 31 patients with pathologic urine protein electrophoresis investigated in this study 9 patients (29%) had additional microalbuminuria and 4 patients (12, 9%) showed increased total urinary protein. ACE inhibitor treatment was subsequently given to 23 patients. 8 patients remained untreated for various reasons. Proteinuria resolved in 74% of patients treated with ACE inhibitors, whereas in the untreated group remission was observed only in 25% (p=0, 014). Improvement of proteinuria was predominantly achieved in patients with recently diagnosed proteinuria, short disease duration and low level of inflammation Conclusions: In patients with SSc and proteinuria, initiation of ACE inhibitor therapy resulted in a significant decrease of proteinuria. Disclosure of Interest: None Declared